Planning Vascular Access in Peritoneal Dialysis—Defining High-Risk Patients. Issue 4 (July 2018) - Ferreira, Hugo; Nunes, Ana; Oliveira, Ana; Beco, Ana; Santos, Joana; Pestana, Manuel
Background: Peritoneal dialysis (PD) is an effective renal replacement technique. However, every year a considerable number of patients are transferred to hemodialysis (HD). Our aim was to identify those at risk, in order to place an arteriovenous fistula (AVF). Methods: Case-control study enrolling all prevalent patients in 2014 and 2015 in our clinic. Groups: 72 case patients who were transferred definitively to HD, 111 control patients (remaining on PD, transplanted, recovered renal function, or deceased). Results: A total of 183 patients were eligible, with a mean age of 55.2 ± 14.8 years, 56.3% male, 31.1% diabetic, and 49.7% on continuous ambulatory PD. The mean follow-up time was 42.1 ± 25.6 months. Eighty-five patients had an AVF. The groups differed in diabetic nephropathy etiology, and in some PD-related characteristics (Kt/V, creatinine clearance, residual renal function, mean ultrafiltration, natriuretic peptide, peritonitis, hospitalizations, and hypervolemia). In multivariate analysis, Kt/V < 1.7 (odds ratio [OR] 3.00, 95% confidence interval [CI]: 1.20 – 7.50], albumin < 35 g/L (OR 4.03, 95% CI: 1.26 – 12.92), number of hospitalizations 1 to 3 (OR 2.74, 95% CI: 1.15 – 6.53) and 4 or more (OR 10.48, 95% CI: 3.62 – 30.36), and 2 or more peritonitis episodes (OR 2.50, 95% CI: 1.03 – 6.07) were predictors of PD transfer to HD. In those patients who were transferred to HD, 34 initiated HD by AVF, 2 needed a catheter due to a non-functioning AVF, and 36 did not have an AVF needing catheter placement. Conclusions: Low Kt/V, low albumin, higher number of hospitalizations, and peritonitis were factors associated with PD transfer to HD, probably indicative of a high-risk PD population where arteriovenous access should be weighed.